24th Annual ASM Conference for Undergraduate Educators (ASMCUE) Late-Breaking Abstracts (American Society for Microbiology, 2017)
Late-breaking abstracts from the 24th Annual ASM Conference for Undergraduate Educators (ASMCUE), held July 27-30, 2017 in Denver, CO.